PERAN MEDIA INTERACTIVE FLAT PANEL DISPLAY (IFPD) DALAM MENINGKATKAN MOTIVASI DAN KOLABORASI BELAJAR SISWA - Renata Tiand Indriansyah (Program Studi Pendidikan Ilmu Pengetahuan Sosial, Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study examines the role of Interactive Flat Panel Display (IFPD) in enhancing students’ motivation and collaboration in Social Studies learning at SD Islam Sabilillah 1 Malang. The research is based on a qualitative case study approach involving purposively selected informants, including a Social Studies teacher and several students. Data were collected through classroom observations, semi-structured interviews, and documentation, and analyzed thematically to identify patterns related to students’ learning motivation and collaborative behavior. The findings reveal two main results: (1) the use of IFPD increases students’ learning motivation by providing visually engaging materials, interactive touch-screen activities, and opportunities for direct involvement through stylus-based participation, which make lessons more dynamic and enjoyable; and (2) IFPD strengthens students’ collaboration, as seen in group discussions, shared problem-solving on the interactive screen, and coordinated use of multi-touch features that encourage collective participation. The study concludes that IFPD serves not only as a technological tool but also as a pedagogical medium that supports active learning, fosters peer interaction, and enriches the overall classroom experience. These findings highlight the importance of integrating digital interactive media in primary education and encourage schools to support teachers through continuous pedagogical and technical training to maximize the benefits of IFPD in instructional practices. ABSTRAK Penelitian ini bertujuan menganalisis peran Interactive Flat Panel Display (IFPD) dalam meningkatkan motivasi dan kolaborasi belajar siswa pada pembelajaran IPS di SD Islam Sabilillah 1 Malang. Penelitian menggunakan pendekatan kualitatif studi kasus dengan informan yang dipilih secara purposive, yaitu guru IPS dan beberapa siswa. Data dikumpulkan melalui observasi kelas, wawancara semi-terstruktur, serta dokumentasi, kemudian dianalisis secara tematik untuk menemukan pola terkait motivasi dan interaksi kolaboratif siswa. Hasil penelitian menunjukkan dua temuan utama: (1) penggunaan IFPD meningkatkan motivasi belajar siswa melalui penyajian materi visual yang menarik, aktivitas layar sentuh yang interaktif, serta keterlibatan langsung menggunakan stylus yang membuat pembelajaran lebih menyenangkan dan mudah dipahami; dan (2) IFPD memperkuat kolaborasi siswa, terlihat dari kerja kelompok yang lebih aktif, diskusi berbasis tampilan layar bersama, serta pemanfaatan fitur multi-touch yang memungkinkan kontribusi simultan dari beberapa siswa. Penelitian ini menegaskan bahwa IFPD tidak hanya berfungsi sebagai perangkat teknologi, tetapi juga sebagai media pedagogis yang mendukung pembelajaran aktif dan interaksi sosial. Hasil penelitian ini mendorong sekolah untuk terus mengintegrasikan media digital interaktif serta menyediakan pelatihan yang memadai bagi guru agar pemanfaatan IFPD semakin optimal.